![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(4x-\sqrt{x^2-4x+4}=4x-\sqrt{\left(x-2\right)^2}=4x-\left(x-2\right)=3x+2\)
b) \(3x+\sqrt{9+6x+x^2}=3x+\sqrt{\left(x+3\right)^2}=3x-\left(x+3\right)=2x-3\)
c) \(\frac{x+6\sqrt{x}+9}{x-9}=\frac{\left(\sqrt{x}+3\right)^2}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\frac{\sqrt{x}+3}{\sqrt{x}-3}\)
d) \(\frac{\sqrt{x^2+4x+4}}{x+2}=\frac{\sqrt{\left(x+2\right)^2}}{x+2}=\frac{\left|x+2\right|}{x+2}\)( 1 )
với x < -2 thì : \(\left(1\right)\Leftrightarrow\frac{-\left(x+2\right)}{x+2}=-1\)
với x > -2 thì : \(\left(1\right)\Leftrightarrow\frac{\left(x+2\right)}{x+2}=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
dk , x lơn hơn hoặc = 0 , x khác 4
\(\frac{\sqrt{x}}{\sqrt{x-2}}\times\frac{x-4}{2\sqrt{x}}+\frac{\sqrt{x}}{\sqrt{x+2}}\times\frac{x-4}{2\sqrt{x}}.\)
có \(x-4=\left(\sqrt{x}-2\right)\left(\sqrt{x+2}\right)\)
\(\frac{\sqrt{x}}{\sqrt{x}-2}\times\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}{2\sqrt{x}}+\frac{\sqrt{x}}{\sqrt{x}+2}+\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}{2\sqrt{x}}\)
rút gọn
\(\frac{\left(\sqrt{x}+2\right)}{2}+\frac{\left(\sqrt{x}-2\right)}{2}\)
\(\frac{2\sqrt{x}}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Rút gọn:
\(A=\sqrt{\frac{1}{x^2-4x+4}}+\frac{-4}{x^2-2^2}\)
\(=\sqrt{\frac{1}{\left(x-2\right)^2}}-\frac{4}{\left(x-2\right)\left(x+2\right)}\)
\(=\frac{1}{x-2}-\frac{4}{\left(x-2\right)\left(x+2\right)}\)
\(=\frac{\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}-\frac{4}{\left(x-2\right)\left(x+2\right)}\)
\(=\frac{x+2-4}{\left(x-2\right)\left(x+2\right)}=\frac{x-2}{\left(x-2\right)\left(x+2\right)}=\frac{1}{x+2}\)
Thay x=3 vào A ta được \(\frac{1}{3+2}=\frac{1}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
P=\(\frac{2\sqrt{x}}{\sqrt{x}+m}+\frac{2\sqrt{x}}{\sqrt{x}-m}-\)\(\frac{m^2}{4x-4m^2}\)
= \(\frac{8\sqrt{x}\left(\sqrt{x}-m\right)+8\sqrt{x}\left(\sqrt{x}+m\right)-m^2}{4x-4m^2}\)
=\(\frac{8\sqrt{x}\left(\sqrt{x}-m+\sqrt{x}+m\right)-m^2}{4x-4m^2}\)
=\(\frac{8\sqrt{x}.2\sqrt{x}-m^2}{4x-4m^2}\)
=\(\frac{16x-m^2}{4x-4m^2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\sqrt{\left(\sqrt{2}\right)^2+2\times2\times\sqrt{2}+2^2}\)+ \(\sqrt{2^2+2\times2\times\sqrt{2}+\left(\sqrt{2}\right)^2}\)
= \(\sqrt{\left(\sqrt{2}+2\right)^2}\)+ \(\sqrt{\left(2-\sqrt{2}\right)^2}\)
= \(\sqrt{2}+2+2-\sqrt{2}\)
= 4